Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Volume 2: Computer Applications/Technology and Bolted Joints 2008
DOI: 10.1115/pvp2008-61214
|View full text |Cite
|
Sign up to set email alerts
|

Valve Packings Seating Stress

Abstract: This paper studies the seating stress required to assure the sealability in valve stems used in high pressure steam service. A test device that simulates the valve stuffing box and a test protocol are proposed. Actual field tests conducted according to a procedure developed from the laboratory tests are also reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Minimum seating stress is the pressure applied by the valve gland, σ 0 , to seat the packing so it fills all the voids between the stem and the stuffing box. These values were determined [10] experimentally using five rings with 6.4mm (1/4in) crosssection and the results are shown in Table 1. The minimum seating stress of each packing style is indicated on the following charts by a red vertical line.…”
Section: Test Results Torque X Axial Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…Minimum seating stress is the pressure applied by the valve gland, σ 0 , to seat the packing so it fills all the voids between the stem and the stuffing box. These values were determined [10] experimentally using five rings with 6.4mm (1/4in) crosssection and the results are shown in Table 1. The minimum seating stress of each packing style is indicated on the following charts by a red vertical line.…”
Section: Test Results Torque X Axial Stressmentioning
confidence: 99%
“…The influence of the number of packing rings on sealability was also investigated. The minimum seating stress calculated on the previous paper [10] for five packing rings was now applied for two and seven rings. It was found that for the four packings studied, the leak rate was equal or less than 0.001mbar-l/sec of He under a pressure of 7bar (102psi).…”
Section: Sealabilitymentioning
confidence: 99%
See 1 more Smart Citation